VD_FINDINFO Jug / 2017 / 36 vom 21. Juli 2016 - VD Tribunal cantonal (2016)
INDEMNITÉ ÉQUITABLE, FRAIS DE LA PROCÉDURE, ACQUITTEMENT | 426 al. 2 CPP (CH), 429 al. 1 let. a CPP (CH), 430 CPP (CH), 433 al. 1 CPP(CH)